Model Pembelajaran Jarak Jauh Di Tingkat SD, SMP, SMA, Dan Perguruan Tinggi Di Kota Pekalongan Selama Pandemi Covid-19 - Dwi Agustina (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah (Bappeda) Kota Pekalongan, 2022)
The implementation of distance learning at schools and educational institutions in Pekalongan City has happened in a sudden due to the covid-19 pandemic. With this sudden implementation of distance learning, there has been no information on how teachers in various educational settings actually implement it and thus the models of distance learning implemented were unknown. There has been no information on the effectiveness and challenges of distance learning either. Thus the writers did a mixed-method study through survey and interview to reveal this information. The respondents were 179 teachers from elementary schools, junior high schools, senior high schools, and universities. The findings show that most teachers perceived the effectiveness of distance learning. However, the models of distance learning varied as teachers in elementary and junior high schools used more asynchronous models while teachers in senior high schools and university levels used more synchronous models. Interestingly, the most frequently used platforms and application were Google Classroom and WhatsApp due to the ease and familiarity. Further, the students’ lack of interest and low independence in learning were seen as the main issues in distance learning. Several other problems were also found which made the distance learning quite problematic in Pekalongan City. Keywords: Distance learning, models, pandemic, mixed-method study